Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/jmr.2804
|View full text |Cite
|
Sign up to set email alerts
|

Molecular toxicity of nanoplastics involving in oxidative stress and desoxyribonucleic acid damage

Abstract: Microplastic pollution attracted extensive attention because of its global presence and adverse effects on ecosystem. However, it is insufficient to clear the effects of nanoplastics on organisms at the molecular level. Herein, a nanopolystyrene (50 nm) was used to examine molecular responses of superoxide dismutase (SOD) and desoxyribonucleic acid (DNA) using spectroscopy (UV-vis, circular dichroism spectra, and fluorescence measurements) and single cell gel electrophoresis methods.Results showed that nanopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 34 publications
(37 reference statements)
0
10
0
1
Order By: Relevance
“…Our research showed a statistically significant increase in lipid peroxidation at a concentration of 0.1 µg/mL in the case of polystyrene nanoparticles with a size of 29 nm, while nanoparticles with a size of 44 and 72 nm caused similar statistically significant changes at the concentration of 1 µg/mL ( Table 2 ). Furthermore, Zheng et al 2019 showed that 50 nm polystyrene nanoparticles increased the level of malondialdehyde (MDA) in rat hepatocytes, being a marker of lipid peroxidation [ 51 ]. Other studies reported a significant increase in lipid peroxidation in the muscle and brain tissue of sea bass ( Dicentrarchus labrax ) after 24-h exposure to microplastics at a concentration of 0.69 mg/L [ 18 , 19 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research showed a statistically significant increase in lipid peroxidation at a concentration of 0.1 µg/mL in the case of polystyrene nanoparticles with a size of 29 nm, while nanoparticles with a size of 44 and 72 nm caused similar statistically significant changes at the concentration of 1 µg/mL ( Table 2 ). Furthermore, Zheng et al 2019 showed that 50 nm polystyrene nanoparticles increased the level of malondialdehyde (MDA) in rat hepatocytes, being a marker of lipid peroxidation [ 51 ]. Other studies reported a significant increase in lipid peroxidation in the muscle and brain tissue of sea bass ( Dicentrarchus labrax ) after 24-h exposure to microplastics at a concentration of 0.69 mg/L [ 18 , 19 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a facultative anaerobe Shewanella oneidensis, riboflavin secretion was altered by PS nanoplastics under aerobic and anaerobic exposures by direct interactions with the cellular membrane and EPS binding (Fringer et al, 2020). In addition to membrane interactions in bacteria, the generation of oxidative stress is one of the most generalized toxicity mechanisms of nanoplastics across the animal taxa (Jeong et al, 2016;Jeong et al, 2018;Miao et al, 2019;Zheng et al, 2019;Hu and Palić, 2020). Oxidative stress induction is associated with further biological responses in bacteria (Sun et al, 2018;Feng J o u r n a l P r e -p r o o f et al, 2019;Saygin and Baysal, 2020).…”
Section: Generation Of Ros and Oxidative Stress In Bacteriamentioning
confidence: 99%
“…Nanoplastics, NPs, categorized as sub-micron-sized plastics [12], are considered contaminants of emerging concern. They are hypothesized to interact and affect living organisms differently compared to larger sized plastic debris, since they may be more easily taken up by organisms, could be more toxic to cells, more easily pass through biological barriers, and may cause oxidative stress and cell death [23]. Moreover, NPs may have the potential to transport further through the environment than larger plastic items due to their smaller size.…”
Section: Introductionmentioning
confidence: 99%